Surfactant protein D and KL-6 serum levels in systemic sclerosis: correlation with lung and systemic involvement - Bonella, F.; Volpe, A.; Caramaschi, et al., P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Objective:The aimof this study was to investigate the relationship between SP-Dand KL-6 serumconcentrations and the extent of interstitial lung involvement, asmeasured by a quantitativeHRCT score and the functional impairment, in patients with systemic sclerosis (SSc).Moreover we analysed the association between these lung-specific biomarkers and skin involvement, anti-Scl-70 antibody titres and an index of disease activity. Methods: Serum SP-D, KL-6 and anti-Scl-70 concentrations were determined by ELISA in 25 SSc patients. Disease activity and lung function parameters were assessed, and the extent of ILD was measured by a HRCT score. Results: SP-D and KL-6 concentrations were higher in patients with SSc and lung fibrosis than in healthy controls. KL-6 correlated positively with the HRCT-fibrosis score (r=0.68, p<0.001), SP-D showed a weaker correlation (r=0.44, p=0.025). Increased KL-6 concentrations were associated with decreased DLCO and decreased FVC in SSc patients, SP-D showed no association. Furthermore KL-6, but not SP-D, showed a strong association with skin involvement as expressed by the modified Rodnan skin score (r=0.71, p<0.0001) and a disease activity index (r=0.73, p<0.0001). Conclusion: KL-6 is more strongly associated than SP-D with the HRCT-fibrosis score, and, different from SP-D, it correlates with skin involvement and disease activity.We suggest that KL-6 may be a useful biomarker in the assessment of scleroderma patients.